HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN HASIL FREE THROW PADA PERMAINAN TIM BOLA BASKET PUTRA SMAN 14 PEKANBARU - Arif, Muhammad; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: this research was done to know it there was relation between the strength of the arm muscle and shoulder. By giving free throw in basketball game in SMAN 14 Pekanbaru. So they could play well and corectly. The population of this research was correlation methode. The population of this research was the basketball players in SMAN 14 Pekanbaru players in SMAN 14 Pekanbaru. The technique of taking samples was the whole population (total sampling). The instrument used in this research was expanding dynamometer. Which is aimed to measure the strength of the arm muscle and shoulder. By giving shooting test free throw. Afterwards, the data was treated with statistic to examine the normality by using lilifors test. In significant level 0,052 the submited hypotethesis was infered that there was a significative relation between the strength of the arm muscle and shoulder by giving free throw in basketball game in SMAN 14 Pekanbaru. According to the analysis of lilifors test generated Lcount (Y) was 0,1157 and Ltable was Ltable was 0,258 and then, Lcount (Y) was 0,1324 and Ltable was 0,258 meant Lcount < Ltable. It meant that the samples were from the normal distributive population. After that, it showed the calculation of product moment correlation was obtained Rcount 0,854 and rtable 0,666 meant rcount > rtable so it made ho was received and Ha was refused.Therefore, there was a significative relation between the strength of the arm muscle and shoulder by giving free throw in basketball game in SMAN 14 Pekanbaru.Keywords: the strength of the arm muscle and shoulder ,by giving free throw